Investigating The Jurisprudential Aspects Of ADR (Journal of Pharmaceutical Negative Results, 2023)
A formal set of guidelines for human conduct is known as the law. Law can be used to govern society. The law has two parts: a descriptive aspect and a philosophical aspect. The philosophical side of the law is covered in jurisprudence. The practise of law is prevalent everywhere. All societies share some commonalities in their jurisprudence, Law (as an institution) is one of several social and political institutions created for conflict settlement. Private parties started looking for novel techniques to speed up the resolution of cases. ADR serves as an alternative to traditional court procedures for resolving disputes. There are two methods for resolving disputes. They are An alternative dispute resolution process and The conventional approach of litigation. Justice has been prioritized by many thinkers, including Plato, above all other moral principles. Overall, justice is a moral principle, but it can take many different forms. Examples include 1. Substantive Justice, 2. Formal Justice, and 3. Legal Justice. The Indian justice system is in a sad state despite being one of the oldest in the world. Indian courts are overburdened with protracted unresolved cases. ADR has developed to strengthen the sense of justice in society because these things are unachievable without it. The aforementioned school of thought has some drawbacks. The main one is that it defines law as a command, regardless of other social structures or institutions. One manifestation of society that was created to address social demands is the law and institutions relating to alternative dispute settlement processes. Artificial intelligence is progressing at an incredibly fast rate. The social, economic, cultural, and political spheres of existence will drastically shift as a result of these advancements. AI systems are starting to appear in ADR processes. Such systems have both advantages and problems. The law ought to be written to take future demands into account.